2019
DOI: 10.5194/acp-19-6147-2019
|View full text |Cite
|
Sign up to set email alerts
|

Ice-nucleating particles in a coastal tropical site

Abstract: Abstract. Atmospheric aerosol particles that can nucleate ice are referred to as ice-nucleating particles (INPs). Recent studies have confirmed that aerosol particles emitted by the oceans can act as INPs. This very relevant information can be included in climate and weather models to predict the formation of ice in clouds, given that most of them do not consider oceans as a source of INPs. Very few studies that sample INPs have been carried out in tropical latitudes, and there is a need to evaluate their avai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
30
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 95 publications
7
30
3
Order By: Relevance
“…between events, possibly due to different composition of the particles or higher sensitivity to atmospheric processing during long-range transport. In general, supermicron particles contributed the most to the INP concentration, in agreement with other previous studies (Mason et al, 2016;Huffman et al, 2013;Ladino et al, 2019). However, our current study is probably the only case in which mineral dust dominated the samples.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…between events, possibly due to different composition of the particles or higher sensitivity to atmospheric processing during long-range transport. In general, supermicron particles contributed the most to the INP concentration, in agreement with other previous studies (Mason et al, 2016;Huffman et al, 2013;Ladino et al, 2019). However, our current study is probably the only case in which mineral dust dominated the samples.…”
Section: Discussionsupporting
confidence: 93%
“…Mason et al (2016) studied the immersion freezing abilities of airborne particles in North America and Europe and found that supermicron particles dominated the freezing, especially at relatively high temperature (258 K). Recent measurements in a coastal tropical site conducted by Ladino et al (2019) also found high concentrations of INPs at relatively high temperatures (> 258 K) due to supermicron particles. In these studies, however, mineral dust is not expected to dominate the samples, and bioaerosol particles are thought to dominate the freezing at high temperatures (> 258 K).…”
Section: Airborne Inp Concentrationsmentioning
confidence: 90%
See 2 more Smart Citations
“…Marine aerosol particles can influence mixed-phase and cirrus cloud formation because a fraction of them are able to act as ice nucleating particles (INPs), facilitating ice crystal formation via different heterogeneous ice nucleation pathways (e.g., Bigg, 1973;Schnell and Vali, 1975;Schnell, 1975Schnell, , 1977Schnell, , 1982Rosinski et al, 1987Rosinski et al, , 1988Mason et al, 2015;DeMott et al, 2016;McCluskey et al, 2017McCluskey et al, , 2018Welti et al, 2018;Si et al, 2018;Creamean et al, 2018;Ladino et al, 2019;Gong et al, 2020). As summarized by Burrows et al (2013), marine microorganisms, EPS aggregates, glassy organics, and crystalline hydrated NaCl are types of aerosol particles that have the potential to nucleate ice in marine environments.…”
Section: Introductionmentioning
confidence: 99%